Tingkat Pengembalian Modal Perbankan: (Bursa Efek Indonesia Tahun 2017-2021) - Ramadani, Fitria; Nafisa, Adita (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2023)
The purpose of this study was to determine the effect of financial performance, activity and bank size on the rate of return on capital (ROE). The design of this study uses a quantitative approach using the purposive sampling method with a sample of 28 banking sector companies listed on the IDX for 2017-2021. The analytical method in this study uses Multiple Linear Regression Analysis. Greetings, this study shows the influence of: (1) Capital Adequacy Ratio (CAR) has significant effect on the Return on Capital (ROE) in Banking listed on the IDX for 2017-2021. (2) The Loan To Deposit Ratio (LDR) has significant effect on the Rate of Return on Equity (ROE) in Banking listed on the IDX for 2017-2021. (3) Non-Performing Loans (NPL) have a significant effect on the Rate of Return on Investment (ROE) in Banking listed on the IDX in 2017-2021. (4) Operating Expenses and Operating Income (BOPO) have a significant effect on the Rate of Return on Investment (ROE) in Banking listed on the IDX for 2017-2021.